PEMANFAATAN MEDIA SOSIAL UNTUK MENINGKATKAN KEPATUHAN MINUM OBAT PASIEN DIABETES MELITUS RAWAT JALAN DI RSUD ULIN BANJARMASIN - Yugo Susanto; Fahma Lailani; Riza Alfian; Leonov Rianto; Dwi Rizki Febrianti; Saftia Aryzki; Erna Prihandiwati; Nurul Shadika Khairunnisa (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2019)
Diabetes mellitus is a group of metabolic diseases with characteristic hyperglycemia that occurs due to abnormal insulin secretion, insulin action or both. WHO predict that by 2030 the number of patients diabetes mellitus in Indoneisa will reach 21,3 million. Patien t compliance is indispensable for achieve theapeutic success. The purpose of this study was to determine the level of medication adherence and differences of the level in medication adherence for outpatient diabetes mellitus patients before and after giving intervestion using sosial media. The sosial media use is whatsapp.The study was conducted with a quasi-experimental design with prospective data taking during period July to August 2018. The subjects who followed study from the beginning to the end of the study were 24 patients with intervention using whatsapp sosial media. Exclusion criteria patients were patients with deaf, illierate and patienets wiht high leves of adherence. Collecting data by interviewing filing out the MARS compliance questioning pre and post intervention on whatsapp sosial media.Based on the result of the study of the level of adherence to medication after intervention were high adherence 83,33% and moderate adherence 16,67%. That was significant adherence difference (p=0,000) of the medication adherence before (22,04±1,57) and after (24,83±0,38). The average change is 2,79±1,19. The result of the study concluded that the interventions using sosial media in patients with diabetes mellitus useful can change pasient adherence in taking medicine. That is indicated by a increase in adherence medication patients (p<0,005).